PENGARUH KOMUNIKASI INTERPERSONAL DAN KOMPETENSI SOSIAL GURU TERHADAP PERILAKU SOSIAL SISWA (Studi Kuantitatif Pada Siswa Madrasah Aliayah Darul Marhamah Cileungsi Bogor Jawa Barat) - EE Junaedi Sastradiharja; Zam'ah (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2021)
This study aims to determine and test empirical data related to interpersonal communication and teacher social competence on eacher social behavior separately or simultaneously In this study the authors used a survey method, with correlational techniques and simple and multiple regression analysis Samples were taken from a population of.83 from a total of 104 student populations at Madrasah Aliyah Darul Marhamah. Data collection techniques using questionnaires, observation, and documentary studies. The data analysis technique used descriptive analysis model, correlation coefficient, simple regression analysis and multiple regression. The type of analysis used is correlation analysis and simple regression and multiple regression which are described descriptively. The results of this study indicate that: First, there is a positive effect of interpersonal communication on students' social behavior based on the results of the partial T test.in.multiple linear.regression analysis, with a large effect of 12.3%, and the simple linear regression equation shows Ŷ = 52.151 + 0.644 X1 which means that every one unit score increase Interpersonal communication, will have an influence on increasing the score of social behavior by 52,794. Second, there is a positive influence on the social competence of teachers on students' social behavior based on the results of the partial T test in multiple linear regression analysis, with a magnitude of influence of 12%, and the simple linear regression equation shows Ŷ = 93.895 + 0.289X2 which means that every one unit increase in the social competency score will have an effect on the increase in students' social behavior scores by 94,184. Third, there is an effect of interpersonal communication and teacher social competence on student social behavior based on the results of the simultaneous F test (F test) in multiple linear regression analysis, with a large effect of 19.8%, and the multiple linear regression equation shows Ŷ = 74.673 + 0.263X1 + 0.234X2. This means that any increase in the score of interpersonal communication and social competence of teachers together or simultaneously, will have an effect on improving student social behavior, amounting to 75.170